Coming clean: the treatment of traces - Wilmot, Cassandra (Rhodes University, Faculty of Humanities, Department of Fine Art, 2013)
Coming Clean is a mixed media installation which aims to address and express ambivalent feelings or notions of loss arising particularly in the absence of a comprehensive narrative or history by focussing on what remains. By researching the role of indexical signs and strategies, particularly as they are deployed by the artist Doris Salcedo, I explore the capacity for these traces to not only effectively mark and memorialise loss, but to also convey the state of loss as experienced by the bereaved without providing a narrative account of the events which preceded them. The domestic ritual of washing is both alluded to and used as a metaphor in etchings, photographic prints and readymade objects to illustrate my concerns, with particular emphasis on the dialectic between what is revealed or concealed. Using representations or traces of this task of laundry to examine this dialectic between concealment and revelation, I comment on the anxiety of dealing with incomplete narrative inheritances by considering how traces of the past which impose themselves on the present may affect both remembrance and the ritual of loss, while also taking into account the complexities behind the disclosure of sensitive information in families.
Keywords: Salcedo, Doris, 1958-; Bereavement in art